Incongruent perceptions of the care values of hospitalized persons with dementia: a pilot study of patient-family caregiver dyads. (3rd April 2018) - Miller, Lyndsey M.; Whitlatch, Carol J.; Lee, Christopher S.; Lyons, Karen S.
ABSTRACT: Objective: Many difficult decisions are made in the inpatient hospital setting regarding the daily care of persons with dementia (PWDs). Incongruent perceptions of the PWD's care values limit the family caregiver's ability to make surrogate decisions. The objectives of this pilot study were to describe and identify determinants of incongruent perceptions in the hospital setting. Methods: Using multilevel modeling (MLM), we examined cross-sectional data collected from 42 PWD-family caregiver dyads. Results: There was a significant amount of incongruence, on average, for all four subscales representing the PWD's care values: autonomy = −0.33 ( p < .001); burden = −.49 ( p < .001); safety/quality of care = −.26 ( p < .001); and social interactions = −.21 ( p = .004). Family caregivers (CG) rated the importance of care values to the PWD as lower than the PWD rated the importance. Determinants of greater incongruence included higher relationship strain and fewer positive dyadic interactions. Conclusion: Our findings reveal significant levels of incongruence in perceptions of the PWD's values among dementia care dyads in the hospital setting. Our analysis suggests a potential impact of relationship variables on incongruence. Further research is needed around this overlooked interpersonal context for supporting the dementia care dyad in the hospital setting.